Madagascar Economic Update, December 2016 - World Bank Group (World Bank, Washington, DC, 2016)
Even though a large majority of poor households are engaged in agriculture, per capita productivity and real levels of sectoral growth remain low in Madagascar. Approximately 80 percent of the population are engaged in agriculture, which provides the main source of income for households, albeit at subsistence levels. Cultivation practices are based on extensification strategies with implications for Madagascar’s fragile natural resource base, rather than improving the productivity of existing farms and land use. To ensure Madagascar’s growth prospects more inclusively benefit the entire population it will be crucial to improve the productivity of the agriculture sector. The first part of the this economic update has the World Bank’s assessment of recent economic developments and the outlook over the short to medium term in Madagascar. The second part of this update focuses on Agriculture and Rural Development.